Begonia piraquara (Begoniaceae) a new species from Atlantic Coastal Forest in the State of Rio de Janeiro, Brazil - Jacques, Eliane De Lima (Phytotaxa, 2023)
Begonia piraquara is a species endemic to the Brazilian Atlantic Rainforest, a biome rich in endemism and species diversity, and is described and illustrated herein. Begonia piraquara resembles to B. fimbritepala E.L.Jacques in the shape of its leaf blades, but differs in having cystoliths (vs. cystoliths absent), staminate tepals with entire to slightly crenulate margins (vs. tepals with ciliate margins).